USING JUMBLED LETTERS TO IMPROVE STUDENTS VOCABULARY MASTERY - Wahyuni, Sri; Rahman, Ali Wira (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2019)
Vocabulary considered one of the important things to learn for students, the vocabulary is basic thing that students must be mastered in foreign language lessons, especially in English. Without vocabulary students will have difficulty in mastering skills in English such as writing, reading, listening and speaking. Therefore, it is very important to find out the solution to enhance students’ vocabulary. The objective of the research is to find out whether or not using Jumbled letters can improve the students vocabulary of the tenth grade students in MAN 2 Barru and to find out whether or not using Crossword puzzle can improve the students vocabulary of the tenth grade students in MAN 2 Barru. This research applied quasi-experimental group design with two groups experimental and control class. The population of this research was the tenth grade students of MAN 2 Barru in academic year 2018/2019. The Total sample of the research was taken by using clustering random sampling which consisted of 141 students. From two classes taken from the population of the tenth grade students of MAN 2 Barru, X MIA 1 as the experimental class consisted 29 students and X MIA 3 as the control class that consisted 29 students. The result of the data analysis showed that there was a significant difference of students’ vocabulary before and after teaching vocabulary through jumbled word letters. The value of t-test pre-test 2.09 was higher than t-table 2.000, and the value of post-test 4.62 was higher than t-table 2.000, at the level significance a =0.05 and degree of freedom (df) = 56. It can be concluded that jumbled word letters can enhance the vocabulary of the tenth grade students’ of MAN 2 Barru